Search for K S 0 $$ K_S^0 $$ invisible decays - The BESIII collaboration; M. Ablikim; M. N. Achasov; P. Adlarson; O. Afedulidis; X. C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; et al. (Journal of High Energy Physics)
Abstract Based on (1.0087 ± 0.0044) × 1010 J/ψ events collected with the BESIII detector at the BEPCII e + e − storage ring, we search for K S 0 $$ K_S^0 $$ invisible decays via the J/ψ → ϕ K S 0 K S 0 $$ φ K_S^0K_S^0 $$ process. No significant signal is observed, and the upper limit of the branching fraction of these invisible decays is set at 8.4 × 10 −4 at the 90% confidence level. This is the first experimental search for K S 0 $$ K_S^0 $$ invisible decays.